An Efficient Genetic Based Algorithm for an Irregular Low Density Parity Check Code with Low Computational Complexity and Low Error Floor - Rathod, D. P.; Awale, R. N. (Advances in Computing, Communication, and Control, 2013)
Very low error rate is necessary for several coding applications like satellite communications, Ethernet transmission, and data storage applications. Therefore, construction of practical tools for anticipating error floors and assessing the success of LDPC codes in the low frame error rate region is necessary. Completely randomly generated codes are good with high probability. The problem that will arise is encoding complexity of such codes is usually rather high as the length of codes increases. We propose an efficient Genetic base algorithm for construction of irregular LDPC codes, which reduces error floor and computational complexity in code design process. Our proposed method is compared with an algorithm in which the codes are generated randomly,. Bit Error Rate (BER), Frame Error Rate (FER) and Computational Complexity are calculated using Matlab platform and compared using both algorithms. Simulations results shows that the codes constructed with proposed method produce low error floors and reduced computational complexity. LDPC Codes based on this design suits for the short block length.